Small Intestinal Obstruction Caused by Anisakiasis. (26th December 2013) - Takano, Yuichi; Gomi, Kuniyo; Endo, Toshiyuki; Suzuki, Reika; Hayashi, Masashi; Nakanishi, Toru; Tateno, Ayumi; Yamamura, Eiichi; Asonuma, Kunio; Ino, Satoshi; Kuroki, Yuichiro; Nagahama, Masatsugu; et al.
Abstract : Small intestinal anisakiasis is a rare disease that is very difficult to diagnose, and its initial diagnosis is often surgical. However, it is typically a benign disease that resolves with conservative treatment, and unnecessary surgery can be avoided if it is appropriately diagnosed. This case report is an example of small intestinal obstruction caused by anisakiasis that resolved with conservative treatment. A 63-year-old man admitted to our department with acute abdominal pain. A history of raw fish (sushi) ingestion was recorded. Abdominal CT demonstrated small intestinal dilatation with wall thickening and contrast enhancement. Ascitic fluid was found on the liver surface and in the Douglas pouch. His IgE (RIST) was elevated, and he tested positive for the anti- Anisakis antibodies IgG and IgA. Small intestinal obstruction by anisakiasis was highly suspected and conservative treatment was performed, ileus tube, fasting, and fluid replacement. Symptoms quickly resolved, and he was discharged on the seventh day of admission. Small intestinal anisakiasis is a relatively uncommon disease, the diagnosis of which may be difficult. Because it is a self-limiting disease that usually resolves in 1-2 weeks, a conservative approach is advisable to avoid unnecessary surgery.